Effect of Ascorbic Acid on Shear Bond Strength of Orthodontic Brackets Bonded with Resin-modified Glass-ionomer Cement to Bleached Teeth - Behnam Khosravanifard; Vahid Rakhshan; Solmaz Araghi; Hadi Parhiz (Tabriz University of Medical Sciences, 2012)
Background and aims. Bleaching can considerably reduce shear bond strength (SBS) of orthodontic brackets bonded with composite adhesives. Application of antioxidants is a method to reverse the negative effect of bleaching on compositeto-enamel bond. However, the efficacy of antioxidants in increasing the SBS of brackets bonded using resin-modified glassionomer cement (RMGIC) has not been studied, which was the aim of this study. Materials and methods. Fifty freshly extracted human maxillary first premolars were bleached with 35% hydrogen peroxide (Pola Office Bleaching, SDI). Sodium ascorbate 10% was applied to the experimental specimens (n=25). All the specimens were etched with 37% phosphoric acid (Ivoclar/Vivadent) and bonded using RMGIC (Fuji Ortho LC, GC). The specimens were subjected to incubation (37°C, 24h) and thermocycling (1000 cycles, 5-55°C, dwell time = 1 min). The SBS was measured at 0.5 mm/min debonding crosshead speed. The adhesive remnant index (ARI) was scored under ×10 magnification. Data were analyzed using Mann-Whitney U test, one- and independent-samples t-test, and Fisher's exact test (α=0.05). Results. The mean SBS of experimental and control groups were 11.97 ± 4.49 and 7.7 ± 3.19 MPa, respectively. The difference was statistically significant (P=0.000 by t-test). SBS of both control (P=0.014) and experimental (P=0.000) groups were significantly higher than the minimum acceptable SBS of 6 MPa, according to one-sample t-test. Conclusion. Application of ascorbic acid can guarantee a strong bond when RMGIC is to be used. However, RMGIC might tolerate the negative effect of bleaching with minimum SA treatments (or perhaps without treatments), which deserves further studies.